2012
DOI: 10.3329/bjpt.v19i1.10935
|View full text |Cite
|
Sign up to set email alerts
|

Pollen morphology of four endemic species of <i>Pedicularis</i> L. from alpine zone of the Deosai Plateau, Himalayan range

Abstract: The pollen morphology with special reference to exine sculpturing of four species of the genus Pedicularis L. has been examined by light and scanning electron microscope. Comparative pollen analysis was made based on the type of pollen, shape in polar and equatorial views, P/E ratio, exine thickness and sculpturing of pollen. In this study, two types of pollen aperture configuration known in the genus were observed i.e., trisyncolpate and bi-syncolpate. Pollen grains with microscabrate ornamentation were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
3
13
1
Order By: Relevance
“…The diversity of pollen and their morphology of 10 plants of Asteraceae species was reported by Ahmad et al () and they concluded that that the chosen species are well established in the region. Bano et al () examined the pollen morphology and few endemic species of Pedicularis from Deosai Plateau. Bano, Ahmad, Zafar, et al () and Shah et al () indicated 50 medicinal species from Deosai Plateau used to cure different ailments by local inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of pollen and their morphology of 10 plants of Asteraceae species was reported by Ahmad et al () and they concluded that that the chosen species are well established in the region. Bano et al () examined the pollen morphology and few endemic species of Pedicularis from Deosai Plateau. Bano, Ahmad, Zafar, et al () and Shah et al () indicated 50 medicinal species from Deosai Plateau used to cure different ailments by local inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 4 types of exine pattern viz., microscabrate-punctate, psilate, microfoveolate-rugulate and medium scabrate-punctate recognized in the present study, of which microfoveolaterugulate exine is reported for the first time in the genus Pedicularis. Bano et al, (2012) also reported microscabrate and psilate exine ornamentation while studying the four endemic species of Pedicularis from Alpine zone of Deosai plateau Himalayan region. However, during the recent treatment by Mill (2015) two species studied by Bano et al, (2012) were no more endemic as they were also reported from other areas.…”
Section: Discussionmentioning
confidence: 88%
“…Bano et al, (2012) also reported microscabrate and psilate exine ornamentation while studying the four endemic species of Pedicularis from Alpine zone of Deosai plateau Himalayan region. However, during the recent treatment by Mill (2015) two species studied by Bano et al, (2012) were no more endemic as they were also reported from other areas.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The variation in ultrastructural characteristics and surface morphology of pollen grains is often of valuable assistance in delimiting taxonomic relationships, particularly at higher taxonomic ranks for family level: Euphorbiaceae (Perveen and Qaiser, 2005), Tiliaceae, Sterculiaceae and Malvaceae (Husseini, 2006), Cucurbitaceae (Perveen and Qaiser, 2008), Campanulaceae (Erkara et al, 2008), for generic level in Sambucus (Tamas et al, 2009), but also between species as in Pedicularis (Bano et al, 2012). Scanning electron microscopy (SEM) is a valuable tool which can reveal many of these taxonomically useful characters, and have the potential to reveal relationships that are obscure and difficult to demonstrate by other means.…”
Section: Introductionmentioning
confidence: 99%